ExacTrac Dynamic workflow evaluation: Combined surface optical/thermal imaging and X‐ray positioning. Issue 10 (24th August 2022) - Da Silva Mendes, Vanessa; Reiner, Michael; Huang, Lili; Reitz, Daniel; Straub, Katrin; Corradini, Stefanie; Niyazi, Maximilian; Belka, Claus; Kurz, Christopher; Landry, Guillaume; Freislederer, Philipp
Abstract: In modern radiotherapy (RT), especially for stereotactic radiotherapy or stereotactic radiosurgery treatments, image guidance is essential. Recently, the ExacTrac Dynamic (EXTD) system, a new combined surface‐guided RT and image‐guided RT (IGRT) system for patient positioning, monitoring, and tumor targeting, was introduced in clinical practice. The purpose of this study was to provide more information about the geometric accuracy of EXTD and its workflow in a clinical environment. The surface optical/thermal‐ and the stereoscopic X‐ray imaging positioning systems of EXTD was evaluated and compared to cone‐beam computed tomography (CBCT). Additionally, the congruence with the radiation isocenter was tested. A Winston Lutz test was executed several times over 1 year, and repeated end‐to‐end positioning tests were performed. The magnitude of the displacements between all systems, CBCT, stereoscopic X‐ray, optical‐surface imaging, and MV portal imaging was within the submillimeter range, suggesting that the image guidance provided by EXTD is accurate at any couch angle. Additionally, results from the evaluation of 14 patients with intracranial tumors treated with open‐face masks are reported, and limited differences with a maximum of 0.02 mm between optical/thermal‐ and stereoscopic X‐ray imaging were found. As the optical/thermal positioning system showed a comparable accuracy to other IGRT systems, and due to its constant monitoring capability, it can be an efficient tool for detecting intra‐fractional motion and for real‐time tracking of the surface position during RT.